2008
DOI: 10.1007/s00066-008-1730-9
|View full text |Cite
|
Sign up to set email alerts
|

Improving Dose Homogeneity in Large Breasts by IMRT

Abstract: Aperture-based IMRT using two tangential incident beam directions, as well as a three-field technique with inverse optimization, provide a better alternative to the standard wedged tangential beams for patients with large breasts treated on low-energy linacs while maintaining the efficiency of the treatment-planning and delivery process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(7 citation statements)
references
References 34 publications
1
6
0
Order By: Relevance
“…In a previous report from our group we worked with a cohort of patients selected because of their unfavorable anatomy, which is probably comparable to their group with the greatest NTCP. Using multifield IMRT a similar order of magnitude of NTCP reduction (3-4% to 0.05% for their sample patient and 6.03% to 0.25% for our patients) could be achieved [48,50,52]. …”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…In a previous report from our group we worked with a cohort of patients selected because of their unfavorable anatomy, which is probably comparable to their group with the greatest NTCP. Using multifield IMRT a similar order of magnitude of NTCP reduction (3-4% to 0.05% for their sample patient and 6.03% to 0.25% for our patients) could be achieved [48,50,52]. …”
Section: Discussionmentioning
confidence: 66%
“…Considering this, it is of interest to notice that APBI delivers a higher maximal dose to parts of the heart as compared to IORT and EBRT. A significantly better sparing of the high-dose volume of the heart in selected early breast cancer patients with unfavourable thoracic geometry has been reported by the use of multifield IMRT [48-50]. Compared to three dimensional conformal radiotherapy (3DCRT), multifield IMRT reduced the heart volume receiving ≥ 30 Gy by 87% [48], or ≥ 35 Gy by 81% [49].…”
Section: Discussionmentioning
confidence: 99%
“…They found lower overall areas of hot spots and lower maximum dose with IMRT. Abo-Madyan et al 23 evaluated intensity-modulated irradiation and other techniques by comparing dose homogeneity, target coverage, feasibility, and dosimetric reliability in patients with large breasts. They observed that aperture-based IMRT using 2 tangential beams with inverse optimization provides a better alternative to the standard wedged tangential beams for patients with large breasts while maintaining the efficiency of the treatment planning and delivery process.…”
Section: Heart Dose Evaluationmentioning
confidence: 99%
“…3 Other researchers have investigated the use of IMRT and hybrid ("open" beams plus optimized beams) techniques for the treatment of breast cancer. [12][13][14][15][16][17][18][19][22][23][24][25][26][27][28] The hybrid treatment planning uses "open" and optimized beams to produce a homogeneous dose distribution, and to decrease the effect of respiratory motion, the "open" beams are usually assigned weights that are as high as possible, and the tangential posterior field edges are matched to spare lung dose. 20,21 There is a lack of consistency among institutions or individuals on what is considered an acceptable treatment plan: target coverage vis-à-vis dose to OAR.…”
Section: Introductionmentioning
confidence: 99%
“…The most common and traditional whole breast radiotherapy technique uses two tangential fields due to its efficiency in terms of sparing nearby organs at risk (OARs) as well as technical simplicity in which wedge filters are used to compensate patient’s surface irregularity and reach a homogenous dose distribution. This technique has evolved over the last decade with the introduction of multi-leaf collimators (MLC) to deliver field-in-field (FIF) three-dimensional conformal (3D-CRT) [ 3 – 6 ] or intensity modulated radiation therapy (IMRT) variants [ 7 11 ].…”
Section: Introductionmentioning
confidence: 99%